On-demand spin-state manipulation of single-photon emission from quantum dot integrated with metasurface - Bao, Yanjun; Lin, Qiaoling; Su, Rongbin; Zhou, Zhang-Kai; Song, Jindong; Li, Juntao; Wang, Xue-Hua (AMER ASSOC ADVANCEMENT SCIENCE, 2020)
The semiconductor quantum dot (QD) has been successfully demonstrated as a potentially scalable and on-chip integration technology to generate the triggered photon streams that have many important applications in quantum information science. However, the randomicity of these photon streams emitted from the QD seriously compromises its use and especially hinders the on-demand manipulation of the spin states. Here, by accurately integrating a QD and its mirror image onto the two foci of a bifocal metalens, we demonstrate the on-demand generation and separation of the spin states of the emitted single photons. The photon streams with different spin states emitted from the QD can be flexibly manipulated to propagate along arbitrarily designed directions with high collimation of the smallest measured beaming divergence angle of 3.17 degrees. Our work presents an effectively integrated quantum method for the simultaneously on-demand manipulation of the polarization, propagation, and collimation of the emitted photon streams.
Keywords: ORBITAL ANGULAR-MOMENTUM